SOME ISSUES OF INTERDISCIPLINARY TEACHING OF MUSIC IN PRIMARY SCHOOL IN UZBEKISTAN (Academia Science Repository, 2023)
The article describes the features and methods of interdisciplinary teaching of music in the primary grades of secondary schools in Uzbekistan.